Global Prices of Crude Oil and the Stock Market Nexus in Indonesia - Januri, Januri (International Journal of Energy Economics and Policy, 2020)
The research intends to analyze the connection among the global prices of crude oil and stock market of Indonesia for the period of 2010 to 2019. The international prices for crude oil attributed to the prices of West Texas Intermediary (WTI) crude oil, whereas the Indonesian stock indices were considered as stock exchange factors in Indonesia. Daily data have been examined using the causal model for LVAR. The findings of he test demonstrated that a cogent and dynamic connection exists between global crude oil prices and the composite indices of Indonesia, in the long as well as short run. The dimensions of this association seem to be positive and thus the composite index also rises (fall) unless the global price of crude oil increases (decreases). Such a result is a required factor for the government's economic policies of Indonesia as well as in the management of its investment patterns by the investors. Keywords: Crude oil, Stock market, Global prices JEL Classifications: E3, R5 DOI: https://doi.org/10.32479/ijeep.10690